The Effect of Asset Growth, Sales Growth and Capital Structure on Financial Distress and Value of the Firm in Sub-Sector Food and Beverage with Good Corporate Governance as Moderation - Dina Octavia Pratiwi; Tri Ratnawati; Achmad Maqsudi (LPPM of NAROTAMA UNIVERSITY, 2023)
Purpose: The value of the firm is an important factor to determine the success of an enterprise. This study has eight problem formulations. Design/methodology/approach: The variables used in this study are asset growth, sales growth, capital structure, financial distress, the value of the firm, and good corporate governance as moderation. The population used in the study was 26 sub-sectors of food and beverage. As a sample, the researchers used many as 13 sub-sector of food and beverage. The research period was three years (2019-2021) during the pandemic Covid-19. Findings: The results of the study showed that asset growth had no effect or was not significant to the value of the firm, sales growth had no effect or insignificant effect on the value of the firm, and capital structure had an effect, in another word it was significant to the value of the firm, asset growth had no effect or was not significant to financial distress, sales growth had an effect or were significant to financial distress, the capital structure was influential and significant to financial distress, financial distress had no effect or insignificant effect on the value of the firm and financial distress with the value of the firm moderated by good corporate governance produces insignificant. Research limitations/implications: Based on the conceptual framework, researchers used Partial Least Square data processing and obtained three significant results, namely capital structure has a significant effect on the value of the firm, asset growth has a significant effect on financial distress and good corporate governance has a significant effect on the value of the firm. While the five influences are not significant. Paper type: Research paper